126. Frequency of Carbapenemases in United States Hospitals (2016-2020) and Activity of Meropenem-Vaborbactam and Comparator Agents Tested Against These Isolates. (15th December 2022) - Castanheira, Mariana; Kantro, Valerie; Hubler, Cory; Mendes, Rodrigo E; Shortridge, Dee
Abstract: Background: We used SENTRY Antimicrobial Surveillance Program data to evaluate the prevalence of carbapenemase enzymes in US hospitals and the activity of meropenem-vaborbactam (MEV) and comparators against these isolates. Methods: A total of 22, 725 Enterobacterales isolates were consecutively collected in 34 US hospitals and susceptibility tested by reference broth microdilution methods. CLSI breakpoints were applied. Carbapenem-resistant Enterobacterales (CRE) isolates, classified by resistance to imipenem or meropenem, were submitted to whole genome sequencing and data analysis for the detection of carbapenemases. Results: Overall, 1.0% (222) of the isolates were CRE. A decrease in CRE prevalence was noted in 2020 (0.8%) compared to 2016 (1.2%). bla KPC variants were detected among 174 (78.4% of the CRE) isolates including 95 bla KPC-3, 75 bla KPC-2, and 1 each of bla KPC-4, bla KPC-6, bla KPC-58, and the Ω-loop variant bla KPC-59. bla SME was detected among 7 S. marcescens . Metallo-β-lactamases (MBLs; 4.0% of the CRE) and OXA-48-like (1.8%) were detected among 9 and 4 isolates, respectively: 7 harbored bla NDM-1/-5 ; 2 isolates carried bla VIM-1 ; and 4 isolates carried bla OXA-48/-232 . MEV (MIC50/90, 0.03/2 mg/L) inhibited 93.2% of the CRE isolates and was the most active agent tested against all isolates. Comparator β-lactam agents had limited activity against these isolates (0 to 5%). Amikacin and tigecycline were the most active comparators and inhibited 78.8% and 95.0% of the CREs, respectively. Ceftazidime-avibactam (CAZ-AVI; MIC50/90, 1/4 mg/L) was tested against 169 (2017-2020) of these isolates, inhibiting 93.5%. Against 181 isolates producing class A serine-carbapenemases, MBV (MIC50/90, 0.03/0.5 mg/L) inhibited 98.9% of all isolates and CAZ-AVI inhibited 99.2% of the 129 isolates collected in 2017-2020. The activity of all agents was limited against MBL producers. Conclusion: The occurrence of carbapenemases declined in the study period, but KPC-producing isolates are dominant among CRE from US hospitals. Small numbers of isolates carrying MBLs and/or OXA-48-like enzymes (< 0.1% of overall) were noted. MEV and CAZ-AVI are very active against isolates producing class A serine-carbapenemases. Disclosures: Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support Valerie Kantro, BA, AbbVie: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Shionogi: Grant/Research Support Cory Hubler, BS, Melinta: Grant/Research Support|Shionogi: Grant/Research Support Rodrigo E. Mendes, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Office for Assistant Secretary of Defense for Health Affairs: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support|Spero Therapeutics: Grant/Research Support Dee Shortridge, PhD, AbbVie: Grant/Research Support|JMI Laboratory: Employee|Melinta: Grant/Research Support|Menarini: Grant/Research Support|Shionogi: Grant/Research Support.